(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores the specific features of psychological adaptation in students within the context of inclusive education. It examines how students, both with and without disabilities, adjust psychologically to inclusive educational settings, addressing emotional, cognitive, and social adaptation processes. The article highlights the challenges students face, such as emotional difficulties, cognitive adjustments, and social integration within a diverse classroom. It also identifies key factors influencing psychological adaptation, including teacher support, peer relationships, family involvement, and the school environment. Furthermore, it discusses strategies to facilitate this adaptation, such as differentiated instruction, promoting positive peer interactions, and ensuring emotional support for students. The article emphasizes the importance of fostering an inclusive culture that benefits not only students with special needs but also enriches the experience of typically developing students.